HISTORY OF INSTITUTIONAL FORMATION AND MODERNIZATION OF THE HORSE-BREEDING SECTOR IN UZBEKISTAN IN THE LAST QUARTER OF THE 20TH CENTURY - Raimov Abdullo Yuzboyevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This paper examines the institutional formation and modernization of the horse-breeding sector in Uzbekistan during the final quarter of the 20th century from a historical-chronological perspective. Within the framework of agricultural history, the study elucidates the transition of the sector into an industrial phase driven by the implementation of the unified TLM 9-83 standards during the 1980–1990s. It demonstrates that the economic and selective breeding baseline established during this period served as a foundational cornerstone for preserving the genetic pool of indigenous breeds and fostering the contemporary development of equestrian sports and tourism.